what must be subtracted from 3x^2-4y^2-5z^2-6 to get 4x^2+5y^2-6z^2+7
Answers
Answered by
10
(3x^2-4y^2-5z^2-6)-(ax^2+by^2+cz^2+d)=4x^2+5y^2-6z^2+7
ax^2+by^2+cz^2+d = -x^2-9y^2+z^2-13
answer is -x^2-9y^2+z^2-13
ax^2+by^2+cz^2+d = -x^2-9y^2+z^2-13
answer is -x^2-9y^2+z^2-13
Answered by
5
Answer:
-x^2 - 9y^2 + z^2 - 13
Step-by-step explanation:
Let the 2nd term be k
3x^2 - 4y^2 - 5z^2 - 6 - k = 4x^2 + 5y^2 - 6z^2 + 7
k = 3x^2 - 4y^2 - 5z^2 - 6 - 4x^2 - 5y^2 + 6z^2 - 7
k = -x^2 - 9y^2 + z^2 - 13
Similar questions